PROPERTIES AND PECULIARITIES OF SPACE-VECTOR-BASED SYNCHRONIZED MODULATION FOR POWER ELECTRONIC CONVERTERS - Oleschuk V.I. (Problems of the Regional Energetics)
This paper presents brief description of peculiarities of a novel method of synchronized pulsewidth modulation (PWM) for power electronic converters. Comprehensive comparison with standard PWM techniques has been done. Basic aspects of practical relevance of new PWM method have been described.